Medical and Surgical Management of Congenital Laryngomalacia: A Case‐control Study. (27th June 2014) - Faria, John; Behar, Philomena
Abstract : Objective: To compare the growth of infants with moderate to severe laryngomalacia who underwent supraglottoplasty to the growth of those treated with medical therapy alone. Study Design: Case‐control study of patients treated between 2008 and 2013. Setting: Tertiary care pediatric otolaryngology practice. Subjects and Methods: Fifty‐one infants newly diagnosed with moderate to severe congenital laryngomalacia. Seventeen infants underwent supraglottoplasty and 34 matched controls had medical management, which included acid suppression therapy, speech and swallowing therapy, and/or high‐calorie formula. The primary outcome measure was weight percentile recorded at the second clinic visit and at the last available follow‐up. The secondary outcomes were the need for primary or revision supraglottoplasty, tracheostomy or gastrostromy, or the development of or persistence of failure to thrive. Results: There was no difference in the mean weight percentile between the surgical and nonsurgical groups at the time of last follow‐up ( P =. 89). The mean change in weight percentile during the study period was 32% (95% CI, 15%‐48%) in the supraglottoplasty group and 31% (95% CI, 22%‐40%) in the medical group ( P =. 97). Five of 5 (100%) patients with failure to thrive managed surgically and 10 of 10 (100%) managed medically were above the fifth percentile at the end of the follow‐up period. One (3%) patient in the medical management group required tracheostomy and gastrostomy tube placement. Conclusions: Medical management and close observation of infants with moderate to severe congenital laryngomalacia may be a viable alternative to supraglottoplasty in appropriately selected infants.